Analysis of sunflower production, at macro and microeconomic level: Case study - Georgiana Rotaru; Mariana Năstase (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
In this study, the production technology of sunflower crop was analyzed, by comparison, in Calarasi county and a company located in Baragan area. The technological system components were analyzed regarding the technology of sunflower crop, practiced in the farm subject to the case study, namely: crop rotation; tillage; fertilization; seed and sowing; maintenance; harvesting. These components are joined by labor force and equipment used, materials and supplies consumed, way of organization and of course, corresponding costs. Also, the study is elaborated by passing from the national plan, to the county medium plan (Calarasi county) and micro, for the studied company with reference to surfaces, production, financial and economic results. The analysis made at macro and microeconomic level highlighted the importance of compliance with the technology fiche plan and with the crop and soil requirements, in terms of materials used, with particular emphasis on varieties and hybrids recently established on the market, which bring great production increases.
Keywords: 330; technology fiche; efficiency; average production; gross margin; crop technology